Motor Fitness Components and Basic Skills as a Function for Discriminating Between Female Volleyball Players (The International Journal for Scientific Research, 2026)
The study aimed to identify the most important motor fitness and technical skill variables that distinguish female volleyball players with high performance from those with low performance. It also sought to develop a discriminant function based on the combined motor fitness and skill variables for differentiating between high- and low-performing female volleyball players.The researchers adopted the descriptive method using the survey approach. The research population consisted of first-division female youth volleyball players for the 2025 season, totaling 168 players. The research sample was selected purposively and included 69 players representing the following sports clubs: Qaraqosh Sports Club, Akad Ankawa Sports Club, Darbandikhan Sports Club, Aphrodite Sports Club, Solaf Sports Club, and North Oil Sports Club.To achieve the objectives of the study, the following tests were administered: seated two-handed overhead medicine ball throw (3 kg); standing long jump; 20-meter sprint test; numbered circles test; standing trunk flexion test; hand-throw accuracy test on overlapping rectangles; standing vertical jump; push-up test; Nelson reaction time test; T-test for agility; one-leg balance test with arms extended sideways and trunk rotation to the right and left for 15 seconds; volleyball serve accuracy test; movement speed test; repeated wall volley test (overhead passing) for 30 seconds; forearm pass (bump) reception accuracy test using thrown balls; repeated blocking test; and cross-court spike accuracy test.Appropriate statistical procedures were applied using the Statistical Package for the Social Sciences (SPSS). based on the analysis, the researchers reached the following conclusions:The researchers reached the following conclusions:-  A discriminant function based on the combined motor fitness and technical skill variables was developed. Three variables were identified as having the greatest discriminative ability between high- and low-performing female volleyball players: leg muscular power, spiking skill and explosive leg power.-  The discriminant function was formulated as follows: Discriminant Function = (Leg Muscular Power × 1.197) + (Spiking Skill × 0.552) + (Explosive Arm Power × 0.109) − 14.142The discriminant function successfully classified the female volleyball players in (the research sample) achieving an overall classification accuracy of 79.7%. Based on these findings, the researchers proposed a number of recommendations.
Keywords: Motor Fitness; Basic Skills; Discrimination Function; Volleyball Players